2020
DOI: 10.1101/2020.11.17.386581
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

LRP1 and SORL1 regulate tau internalization and degradation and enhance tau seeding

Abstract: The identification of the apoE receptor, LRP1, as an endocytic receptor for tau raises several questions about LRP1s’ role in tauopathies. Is internalized tau, like other LRP1 ligands, delivered to lysosomes for degradation? Does LRP1 internalize pathological tau leading to cytosolic seeding? Do other, related receptors participate in these processes? We confirm that LRP1 rapidly internalizes tau, leading to efficient lysosomal degradation. Employing brain homogenates from human Alzheimer brain, we find that L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 99 publications
(118 reference statements)
0
5
0
Order By: Relevance
“…Furthermore, knockdown of LRP1 in neurons dramatically suppresses tau spread across the brain in the mouse unilaterally injected with AAV expressing human tau with P301L mutant in hippocampus (Rauch et al, 2020), suggesting that LRP1 may represent a novel therapeutic target for tauopathies. Internalization of tau by LRP1 was further demonstrated using 125 I-labeled recombinant 2N4R tau in LRP1deficient CHO cells (Cooper et al, 2020). The direct binding of 2N4R tau monomer with LRP1 was confirmed utilizing surface plasmon resonance (SPR) analysis.…”
Section: The Interaction Of Tau With Membrane Proteinsmentioning
confidence: 89%
See 2 more Smart Citations
“…Furthermore, knockdown of LRP1 in neurons dramatically suppresses tau spread across the brain in the mouse unilaterally injected with AAV expressing human tau with P301L mutant in hippocampus (Rauch et al, 2020), suggesting that LRP1 may represent a novel therapeutic target for tauopathies. Internalization of tau by LRP1 was further demonstrated using 125 I-labeled recombinant 2N4R tau in LRP1deficient CHO cells (Cooper et al, 2020). The direct binding of 2N4R tau monomer with LRP1 was confirmed utilizing surface plasmon resonance (SPR) analysis.…”
Section: The Interaction Of Tau With Membrane Proteinsmentioning
confidence: 89%
“…The direct binding of 2N4R tau monomer with LRP1 was confirmed utilizing surface plasmon resonance (SPR) analysis. In the SPR analysis, 2N4R tau isoform showed higher affinity for LRP1 than 2N3R tau isoform, suggesting that the R2 domain of tau is important for their binding (Cooper et al, 2020). In the same study, Cooper and colleagues showed that phosphorylation of tau reduces its affinity for LRP1 by comparing binding affinity of 2N4R tau isoform and its phosphomimetic form.…”
Section: The Interaction Of Tau With Membrane Proteinsmentioning
confidence: 98%
See 1 more Smart Citation
“…Future studies in which expression of these receptors are experimentally modulated (i.e., knockdown, overexpression) in the context of APOE isogenic lines with various fAD-related mutations will need to be performed to further probe these relationships. With respect to neurons, recent work has shown that LDLR and LRP1 facilitate the endocytosis of tau and its subsequent spread [84,85]. In this regard, future studies that examine the ApoE isoform-dependent relationship between neuronal expression of LDLR/LRP1 and tau uptake would be of interest in elucidating the effects of APOE2 on the mitigation of AD-related phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The amyloid beta peptides can bind to various receptors in the brain, including N-methyl-D-aspartate (NMDA), which plays a key role in learning and memory, Alpha7 nicotinic acetylcholine receptor (α7nAChR), which is involved in the regulation of neurotransmitter release, and receptor for advanced glycation end products (RAGE), which is involved in the immune response [ 179 , 180 , 181 ]. Tau proteins have been shown to bind to several receptors, including the low-density lipoprotein receptor-related protein 1 (LRP1) [ 182 , 183 ] and the sortilin-related receptor (SORL1) [ 184 , 185 , 186 ]. These receptors are involved in the transport of proteins within cells, and are thought to play a role in the clearance of tau from the brain [ 187 ].…”
Section: The Current Stage Of Ad Treatments: Targeting the Usual Culp...mentioning
confidence: 99%